EFFECTIVENESS OF VILLAGE INFORMATION SYSTEMS IN THE LARANGAN VILLAGE GOVERNMENT - Agustiuns, Kandina Bahagia; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the effectiveness of the Village Information System (SID) in supporting governance and public services in the Larangan Village Government. Method: A qualitative approach was employed, with data collected through in-depth interviews and direct observations to capture the performance of SID in practice. Results: Findings reveal that the effectiveness of SID can be explained through three main approaches: the source approach, where the quality of human resource management significantly influences system performance, though challenges remain for elderly users with limited digital literacy; the process approach, which highlights community satisfaction as a measure of service quality and alignment with public needs; and the goal approach, which emphasizes the achievement of organizational objectives through transparency, adaptability, and community participation in village development. Novelty: This study provides a comprehensive evaluation of SID effectiveness by integrating three theoretical approaches to organizational effectiveness, offering practical insights into digital governance at the village level and highlighting the importance of inclusivity and adaptability in the era of technological transformation.